2019
DOI: 10.1177/0954410019872089
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of an axisymmetric divergent dual throat nozzle

Abstract: The dual throat nozzle achieves higher thrust vectoring efficiencies and lesser thrust loss than other fluidic thrust-vectoring nozzles. Separation always occurs at the bottom of the cavity with complex three-dimensional characteristics for the dual throat nozzle. In this paper, by comparing the flow structure, nozzle surface static pressure distributions and skin friction lines, which are obtained by numerical simulations and wind tunnel experiments, an axisymmetric divergent dual throat nozzle is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…They have been used in many real supersonic fighters, such as F-22 Raptor, F-15S/MTD, and SU-27 Flanker. Wang et al (2019b) experimentally confirmed the real flow features in the conical DTN are not fully axisymmetric based on oil flow visualization technology. It is not well demonstrated that if this asymmetric flow characteristic would occur in a 3-D rectangular DTN.…”
Section: Fig 1 Illustration Of Aircraft Axessupporting
confidence: 53%
See 1 more Smart Citation
“…They have been used in many real supersonic fighters, such as F-22 Raptor, F-15S/MTD, and SU-27 Flanker. Wang et al (2019b) experimentally confirmed the real flow features in the conical DTN are not fully axisymmetric based on oil flow visualization technology. It is not well demonstrated that if this asymmetric flow characteristic would occur in a 3-D rectangular DTN.…”
Section: Fig 1 Illustration Of Aircraft Axessupporting
confidence: 53%
“…All nozzle and slot injection syringe surfaces are assumed as adiabatic walls. Other exit boundaries are taken as the pressure outlet boundary.All current CFD work is finished in the software of Fluent that is good at calculating incompressible and compressible flows based on pressure-based and density-based solvers(Lin et al 2020;Tao et al 2020;Wang et al 2019a;Wang et al 2019b). By referring to earlier references(Deng and Kim 2015;Vignesh et al 2016;Vignesh et al 2019;Wu and Kim 2019a;Raman et al 2020;Wu et al 2020a), the density-based solver is fixed for issues of compressible flow.…”
mentioning
confidence: 99%
“…11,34,35 Also several numerical investigations about BDTN or conventional DTN flows have used the same boundary conditions. 12,13,16,17…”
Section: Methodsmentioning
confidence: 99%
“…Also Wang et al. 17 prove that the actual flow in the axisymmetric divergent dual throat nozzle (ADDTN) indeed possesses three-dimensional characteristics by comparing the flow structure, nozzle surface static pressure distributions and skin friction lines, which are obtained by numerical simulations and wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The standard ambient pressure is kept constant at 101325 Pa. The stagnation temperatures of the injected and primary streams have a constant value of 297.04 K. In past validation studies, Wang et al [22] attempted to validate their numerical research methodology with the Spalart-Allmaras, realizable k-epsilon (kε), and SST k-ω turbulence models and elaborated on that the SST k-ω turbulence model gives the best accuracy in agreement with the experimental result. Consequently, the SST k-ω turbulence model is performed to verify our present research methodology.…”
Section: Experimental Verificationmentioning
confidence: 99%